Ukraine Agricultural Competitiveness - World Bank (Washington, DC, 2014)
The agri-food sector is an important part of the Ukrainian economy. Agriculture could make an even larger contribution to economic growth and the vitality of rural areas in Ukraine than is currently the case. Ukraine has the agro-climatic potential to be a major player on world agricultural markets. Agricultural competitiveness in Ukraine also suffers from inadequate systems to test and document food product quality and food safety. Ukraine's food safety control system is complicated and characterized by fragmented and often overlapping jurisdictions. Many standards applied in Ukraine are inconsistent with World Trade Organization (WTO) provisions, with standards established by the responsible international bodies and with accepted practices in international trade. Without improvements towards an efficient and internationally recognized food quality and safety control system, Ukrainian agriculture will find it increasingly difficult to sell into international markets and its products will not be able to command top prices. The ban on Ukrainian meat, eggs, fish, cheese, milk and butter imposed by Russia in mid-January 2006 provides an example of the disruptions that can result. This negative impact on competitiveness will be increasingly acute for more perishable products, higher-processed products and products that combine different agricultural raw materials - in other words many high-value added products. Policy reforms and investments could greatly increase the competitiveness of Ukrainian agriculture. In the policy sphere, greater restraint should be exercised in the area of trade, market and price policy. Ad hoc intervention on agricultural markets should be reduced. Accession to the WTO is an important and encouraging signal that policy makers are willing to adopt less intrusive and more stable trade, market and price policies. In the investment sphere, priorities include food safety monitoring and certification systems, trade infrastructure and logistic capacity, food chain management, technical advisory and market information systems, streamlined and transparent customs procedures, land markets, and research and education institutions.